1997
DOI: 10.3109/10641959709031637
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Degranulation Activity in Preeclampsia

Abstract: Objective: Our purpose was to characterize neutrophil degranulation activity related to the manifestation of preeclampsia. Materials and Methods: Studied were nine nonpregnant healthy women, nine normal pregnant women, and six cases with preeclampsia in the third trimester. Neutrophil preparations obtained for each case were divided into one nonstimulation and two stimulation groups using 10 and 100 nmol/L of N-formyl-methionyl-leucyl-phenylalanine (FMLP). Main Outcome Measure: [)-glucuronidase activity measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…19 Studies on circulating neu trophils demonstrate that neutrophil degranulation is already activated in preeclampsia, with a de crease in the total granule content retained in the neutrophil. 20 This activation could have occurred in the placental bed prior to returning to the mater nal circulation. T and B cells may also be involved.…”
Section: The Maternal Immunological Responsementioning
confidence: 99%
“…19 Studies on circulating neu trophils demonstrate that neutrophil degranulation is already activated in preeclampsia, with a de crease in the total granule content retained in the neutrophil. 20 This activation could have occurred in the placental bed prior to returning to the mater nal circulation. T and B cells may also be involved.…”
Section: The Maternal Immunological Responsementioning
confidence: 99%
“…For instance, studies using luminol chemilu‐minescence have shown a trend for increased respiratory burst activity during pregnancy 24 , while those employing more selective measurements of superoxide anions, such as lucigenin, have shown a consistent reduction 25 . More recently, Tsulumori et al 26 reported an increase in the respiratory burst of neutrophils during pre‐eclampsia using the superoxide dismutase‐inhibitable reduction of femcytochrome C. Although employing a direct measurement of superoxide anion release‐similar to that of lucigenin chemiluminescence‐this study could not be repeated or substantiated in preliminary studies by Ama‐gase el at 27 …”
Section: Discussionmentioning
confidence: 80%
“…However, the role of β-glucuronidase in the context of bovine pregnancy has been poorly elucidated and very limited literatures are available depicting its significant role during pregnancy. Amagase et al (1997) reported no significant difference in the β-glucuronidase activity in the neutrophils of the non-pregnant and the normal pregnant women. However, in contrast to this, we noted significantly reduced level of β-glucuronidase activity in the neutrophils obtained from the pregnant cows.…”
Section: Discussionmentioning
confidence: 91%